2019
DOI: 10.3390/toxins11090484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spider (Phlogiellus genus) Phlotoxin 1 and Synthetic Variants as Antinociceptive Drug Candidates

Abstract: Over the two last decades, venom toxins have been explored as alternatives to opioids to treat chronic debilitating pain. At present, approximately 20 potential analgesic toxins, mainly from spider venoms, are known to inhibit with high affinity the NaV1.7 subtype of voltage-gated sodium (NaV) channels, the most promising genetically validated antinociceptive target identified so far. The present study aimed to consolidate the development of phlotoxin 1 (PhlTx1), a 34-amino acid and 3-disulfide bridge peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…No neurotoxicity found (Deuis et al, 2017;Goncalves et al, 2019;Nicolas et al, 2019) JzTx 34 610 Effective in reducing formalin-induced, acetic acid-induced, and thermal pain in mice. As efficacious as morphine (i.p.…”
Section: Discussionmentioning
confidence: 99%
“…No neurotoxicity found (Deuis et al, 2017;Goncalves et al, 2019;Nicolas et al, 2019) JzTx 34 610 Effective in reducing formalin-induced, acetic acid-induced, and thermal pain in mice. As efficacious as morphine (i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Phlotoxin 1 (Ph1Tx1) is a 34-residue toxin purified from Phlogiellus spider venom, a promising antinociceptive peptide with a high affinity for Pav [ 128 ]. The crude venom of Phoneutria nigriventer (armed spiders), besides its antineoplastic activity, can suppress the IFN-γ release and increase the expression of the anti-inflammatory cytokine IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…Database search of the monoisotopic oxidized peptide masses of the whole and fractionated spider venom from P. bundokalbo showed that all the peptide masses were not similar to masses of 3 isoforms of peptides from Phlogiellus sp. recorded on Arachnoserver which are µ-theraphotoxin-Phlo1a (4103.79 Da), µ-theraphotoxin-Pho1b (4137.78 Da), and µ-theraphotoxin-Phlo2a (N-terminal fragment) (3276.33 Da) [ 45 , 55 , 56 ]. On the other hand, some of the peptides present in the whole and fractionated venom have similar masses present in the database from other species of spider that are related to P. bundokalbo by family and order as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%